1998
DOI: 10.1016/s0014-5793(98)01189-2
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar phorbol ester binding properties of the individual cysteine‐rich motifs of protein kinase D

Abstract: Protein kinase D (PKD) is a serine/threonine kinase that binds phorbol esters in a phospholipid-dependent manner via a tandemly repeated cysteine-rich, zinc finger-like motif (the cysteine-rich domain, CRD). Here, we examined whether the individual cysteine-rich motifs of the CRD of PKD (referred to as cys1 and cys2) are functionally equivalent in mediating phorbol ester binding both in vivo and in vitro. Our results demonstrate that the cys1 and cys2 motifs of the CRD of PKD are functionally dissimilar, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 30 publications
1
76
0
Order By: Relevance
“…DAG binding to PKD is proposed to colocalize PKCs to facilitate Ser-744/Ser-748 phosphorylation, but the role of DAG binding to PKD1 for enzyme activation in lymphocytes has not been fully assessed. Previous studies have shown that PKD-P287G, a PKD1 mutant with a mutated C1b domain that has lost ϳ90% of its DAG/phorbol ester binding capacity, can still be activated in response to antigen receptor triggering (6,29). However, this result does not fully resolve the role of DAG binding for PKD1 activation because PKD-P287G has residual capacity to bind DAG/phorbol esters via its low affinity C1a domain.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…DAG binding to PKD is proposed to colocalize PKCs to facilitate Ser-744/Ser-748 phosphorylation, but the role of DAG binding to PKD1 for enzyme activation in lymphocytes has not been fully assessed. Previous studies have shown that PKD-P287G, a PKD1 mutant with a mutated C1b domain that has lost ϳ90% of its DAG/phorbol ester binding capacity, can still be activated in response to antigen receptor triggering (6,29). However, this result does not fully resolve the role of DAG binding for PKD1 activation because PKD-P287G has residual capacity to bind DAG/phorbol esters via its low affinity C1a domain.…”
Section: Resultsmentioning
confidence: 93%
“…The Role of the PKD1 CRD in PKD1 Activation in Lymphocytes-There are two cysteine-rich motifs (C1a and C1b) within the CRD of PKD1 that are required for the enzyme to bind DAG with high affinity and control the intracellular localization of the enzyme (26,29,33). DAG binding to PKD is proposed to colocalize PKCs to facilitate Ser-744/Ser-748 phosphorylation, but the role of DAG binding to PKD1 for enzyme activation in lymphocytes has not been fully assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the PH domain can activate PKD1 [17,24,25] . Deletion of the two zinc-fi ngers also fully activates PKD1 [26,27] .…”
Section: The Pkd Family Belongs To the Camk Groupmentioning
confidence: 99%
“…Mutations in the PH domain can activate PKD1 [17,24,25] . Deletion of the two zinc-fi ngers also fully activates PKD1 [26,27] .PKD transportation to different destinations, such as the plasma membrane, nucleus, or Golgi apparatus, in response to different signaling pathways, is largely dependent on the interactions of the PKD regulatory domains with lipids or proteins. In resting cells, PKD is mostly located in the cytosol, with a smaller fraction in the Golgi apparatus.…”
mentioning
confidence: 99%